Pengaruh Financial Leverage, Sales Growth, Interest Rate, dan Inflasi terhadap Kinerja Pasar (Studi Empiris pada Perusahaan Tekstil dan Garmen yang terdaftar di Bursa Efek Indonesia) - Ferviani, Sari B1021141009 (Jurnal Manajemen Update, 2018)
This study aims to explain the effects of financial leverage, sales growth, interest rate and inflation on market performance on textile and garment companies listed in Indonesia Stock Exchange (IDX) period 2011-2016. The sample in this study was conducted on 18 companies taken by using purposive sampling method. This study used regression analysis technique of panel data. Analysis model in this study used control variable that was firm size. The result of the study was partially stated that financial leverage proxied by long term debt to equity ratio, variable of interest rate and inflation had insignificant effect on market performance which was proxy by earning per share, while sales growth had positive and significant influence to market performance.